2011
DOI: 10.2355/isijinternational.51.1601
|View full text |Cite
|
Sign up to set email alerts
|

Catalyzing Carbothermic Reduction of Siderite Ore with High Content of Phosphorus by Adding Sodium Carbonate

Abstract: The characteristics of Huimin siderite ore with high content of phosphorus and the reduction of this ore bearing pulverized coal and sodium carbonate were investigated. The study focuses on the influence of Na2CO3 dosage on the carbothermic reduction process. Iron particle size in reduced ore is tiny and the fayalite is abundant without Na2CO3 additive. With ratio of Na2CO3 to ore at 1:20 or 1:10, iron particle size in reduced ore is coarse and the diffraction intensity of metallic iron increases obviously in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 10 publications
0
23
0
Order By: Relevance
“…S.J. Bai et al 21) had report- Note: x for FeOx was calculated as index for Fe reduction degree (0<x<1.5). ed that the formation of fayalite (2FeO·SiO2) is the main hindrance for the rapid reduction of siderite and adding appropriate amount of Na2CO3 optimized the reduction.…”
Section: Thermodynamic Considerationmentioning
confidence: 99%
“…S.J. Bai et al 21) had report- Note: x for FeOx was calculated as index for Fe reduction degree (0<x<1.5). ed that the formation of fayalite (2FeO·SiO2) is the main hindrance for the rapid reduction of siderite and adding appropriate amount of Na2CO3 optimized the reduction.…”
Section: Thermodynamic Considerationmentioning
confidence: 99%
“…Conversely, lower the reduction temperature is beneficial for the dephosphorization during the coal-based reduction process, while it will hinder the reduction rate of the reduced product. Therefore, E. Matinde, 16,17) S. J. Bai 18) and W. Yu 19) have widely investigated the function of dephosphorization by adding Ca(OH) 2 and Na 2 CO 3 on the coal-based reduction, the experiment results show that the additives is beneficial for the dephosphorization during the ore-carbon reduction in a semi-molten state.…”
Section: Introductionmentioning
confidence: 99%
“…According to thermodynamic data of the reactions between the H 2 /CO and the ore phases, the iron oxide can be reduced by reducing gas at low temperature, while the apatite is hard to be reduced in the temperature range of 300 K to 1 900 K. 5,[18][19][20] L. Guo,20) Z. L. Zhao and H. Q. Tang 21,22) have investigated the gas-based reduction by H 2 /CO at the temperature of 1 073 K to 1 273 K, the results show that gaseous reduction in fluidized bed or in static state can both reach a high reduction extent of iron oxide with the phosphorus still exists in apatite. Recently, M. Omran [23][24][25] and H. Q. Tang 26) have studied the function of microwave heating on the structure of high phosphorous oolitic iron ores, and they both found that the oolitic unit generated cracks and fissures due to microwave, and the microwave treatment can improve the phosphorus separation and magnetic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The recent studies indicated that metallization reductive roasting followed by magnetic separation is efficient for separating and recovering iron from refractory iron-containing ores, and sodium salts (e.g., sodium carbonate and sodium sulfate) are the appropriate additives for improving the iron separation in the process [16][17][18][19][20][21]. A recent study by the authors [22] has confirmed that 92.51% of iron was separated and a powdered direct reduction iron (DRI) with 88.17% total iron content (TFe) was obtained under the optimal conditions.…”
Section: Introductionmentioning
confidence: 99%